Developing Eco-Friendly Biopolymers for Reducing Plastic ‎Pollution - Venkatesan , Dr. D.; Sunil , M. P.; Kolaventi , Dr Swarna Swetha; Sharma, Divya; Nanda , Dr. Binita; Goyal , Prakhar; Singla, Abhishek (International Journal of Basic and Applied Sciences, 2025)
Polymers have many applications and have grown increasingly vital to everyday existence. The utilization of polyethylene has escalated ‎twenty-five times over the previous fifty years and is projected to double in the subsequent years. Globally, around 325 million tons of ‎polyethylene are generated annually. The manufacturing, utilization, and removal of polymers have become a chronic and significant hazard ‎to the surroundings. The incorrect elimination of polymers contaminates the ecosystem, leading to the yearly demise of thousands of ‎organisms and a decline in soil quality. Biodegradable plastics and Biopolymers (BP) derived from different forms of life may serve as ‎substitutes for artificial polymers. BP may be derived from organic feedstock supplies, including carbohydrates, cellulose, pectin, ‎collagen, and gelatin. All these BP have appropriate physicochemical, heat, and mechanical qualities that render them acceptable for natural ‎and Eco-Friendly BP (EF-BP) manufacturing that mitigates plastic pollution (PP). The application of BP extends beyond bioplastics to ‎include the sustainable manufacturing of many goods, including implantable devices, biological fuels, and pharmaceuticals. This study fully ‎examines the components of BP, their extraction and purifying processes, and the factors that make them effective for environmental ‎applications‎.
Keywords: Polymers; Biopolymers; Plastic Pollution; Sustainability; Eco-friendly; Ecosystem